2018
DOI: 10.1177/0218492318773237
|View full text |Cite
|
Sign up to set email alerts
|

Chronic contained abdominal aortic aneurysm rupture causing vertebral erosion

Abstract: Erosion of vertebral bodies by an abdominal aortic aneurysm is extremely rare. Chronic contained rupture can cause difficulties in diagnosis because there are many clinical presentations: back pain, sciatic pain, or an expansive abdominal mass. Computed tomography is the gold-standard diagnostic tool. We report the case of a 49-year-old man who suffered from back pain because of a chronic ruptured aortic aneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Chronic-contained rupture of aortic aneurysm was first described by Szilagyi et al 2 and Galessiere et al 3 Since the initial description, less than 100 similar cases have been documented worldwide. 4 Its presentation is distinctly different from that of acute rupture of aortic aneurysm.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Chronic-contained rupture of aortic aneurysm was first described by Szilagyi et al 2 and Galessiere et al 3 Since the initial description, less than 100 similar cases have been documented worldwide. 4 Its presentation is distinctly different from that of acute rupture of aortic aneurysm.…”
Section: Discussionmentioning
confidence: 98%
“… 5 Booth and Galland 7 reported that the clinical features of contained AAA rupture are vague with back pain in 64% of cases, abdominal pain in 20%, groin pain in 14%, femoral neuropathy in 8%, sepsis in 10%, and asymptomatic in 8%. 4 The clinical presentation may masquerade as metastatic carcinoma, infectious spondylitis, retroperitoneal infection, psoas abscess, and, rarely, obstructive jaundice. 8 The mechanism of chronically contained AAA rupture is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, we expect to further enrich the variability of the training data by improving the physical models or collecting more patient data to incorporate the marginal situations. Specifically, we generate a large amount of data by varying three parameters in the computational G&R simulations, which may not be enough to capture all the different features in actual AAA evolution, e.g., intraluminal thrombus [50,52,53], other morphological parameters [54,55], and influence of surrounding tissues [56,57]. Hence, more parameters and more complex models will be carefully selected in the future to provide better simulation-based training data.…”
Section: Discussionmentioning
confidence: 99%
“…A CCR-AAA is a well-known, extremely rare subtype of AAA that was first reported by Szilagyi et al in 1961 [13]. It is characterized by low blood loss and stable hemodynamics, which are due to hemostasis by tissue peripheral to the retroperitoneum when the aortic aneurysm ruptures [4, 5].…”
Section: Discussionmentioning
confidence: 99%